The Risks of Complications During Endoscopic Sinus Surgery in Cystic Fibrosis Patients: An Anatomical and Endoscopic Study. (19th January 2021) - Maggiore, Giandomenico; Pietragalla, Michele; De Amicis, Christian; Nardi, Cosimo; Bruno, Chiara; Gallo, Oreste; Bonasera, Luigi; Perrone, Anna; Cavallo, Annalisa; Colagrande, Stefano; Taccetti, Giovanni; Locatello, Luca Giovanni
Abstract : Objective/Hypothesis: An increasing proportion of adult cystic fibrosis (CF) patients is being referred to endoscopic sinus surgery (ESS) in order to relieve the symptoms of chronic rhinosinusitis (CRS). Given that CFTR mutations profoundly alter sinonasal development, we want to explore the relationship between their peculiar surgical anatomy and the risk of postoperative complications. Study Design: Retrospective case‐control study. Methods: Paranasal sinuses CT scans of 103 CF adult patients with CRS were compared to those belonging to a cohort of 100 non‐CF adult patients to explore their anatomical differences. Secondly, CF and non‐CF patients who received primary/revision ESS were analyzed in order to assess their preoperative CT scan in terms of surgically relevant variants, and according to the CLOSE checklist. Surgical outcomes were statistically compared in order to explore the differences between groups. Results: CF group presented more frequently with smaller and less pneumatized paranasal sinuses and a higher Lund‐Mckay score compared with controls. No anatomical differences emerged in terms of genotype stratification. Non‐CF CRS patients undergoing ESS showed a significantly deeper olfactory fossa and a more frequent supraorbital pneumatization compared to CF patients ( P  < .001 and P  = .031, respectively). Whereas this latter group underwent more often aggressive surgical procedures ( P  = .001), no difference in terms of postoperative adverse events was found ( P  = .620). Conclusions: Despite receiving more often aggressive ESS procedures, adult CF patients do not show an increased risk of postoperative complication and this may be linked to a different proportion of anatomical and surgically‐relevant variants. Level of Evidence: 4 Laryngoscope, 131:E2481–E2489, 2021